Fun projects: Transportation - BPI India (New Delhi : BPI India Ltd, 2011)
Fun projects is a series of ten books for young learners, science has lively pages of relevant text, fantastic pictures, free stickers plus informative fat cards. Science is the systematic study of the physical and biological world through observations, measurements and experiments. This book gives information about everything scientific in a fresh, fun and interactive way. Open this book and learn about science while having lots of fun. 1: Make fun projects with special features of this amazing book. 2: Loads of information on relevant subjects. 3: Colorful stickers pertaining to every topic. 4: Perforated cards full of interesting tidbits and illustrations.
Location: 4B
Keywords: Book